A low-carbohydrate diet containing soy protein and fish oil reduces breast but not prostate cancer in C3(1)/Tag mice. (27th December 2021) - Elisia, Ingrid; Yeung, Michelle; Wong, Jennifer; Kowalski, Sara; Larsen, Meegan; Shyp, Taras; Sorensen, Poul H; Krystal, Gerald
Abstract: We recently showed that a low-carbohydrate (CHO) diet containing soy protein and fish oil dramatically reduces lung nodules in a mouse model of lung cancer when compared to a Western diet. To explore the universality of this finding, we herein compared this low-CHO diet to a Western diet on in preventing breast and prostate cancer using a mouse model that expresses the SV40 large T-antigen specifically in breast epithelia in females and prostate epithelia in males. We found that breast cancer was significantly reduced with this low-CHO diet and this correlated with a reduction in plasma levels of glucose, insulin, IL-6, TNFα and prostaglandin E2 (PGE2). This also corresponded with a reduction in the Ki67 proliferation index within breast tumors. On the other hand, this low-CHO diet did not reduce the incidence of prostate cancer in the male mice. Although it reduced both blood glucose and insulin to the same extent as in the female mice, there was no reduction in plasma IL-6, TNFα or PGE2 levels, or in the Ki67 proliferation index in prostate lesions. Based on immunohistochemistry studies with antibodies to 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 (PFKFB3), carnitine palmitoyltransferase Ia (CPT1a) and fatty acid synthase (FAS), it is likely that this difference in response of the two cancer types to this low-CHO diet reflects differences in the glucose dependence of breast and prostate cancer, with the former being highly dependent on glucose for energy and the latter being more dependent on fatty acids. Abstract : A low-carbohydrate diet containing soy protein and fish oil reduced breast cancers but not prostate cancers in mice expressing the SV40 large T-antigen specifically in breast and prostate epithelia, because the breast cancers were more dependent on glucose. Graphical Abstract: